Discussing the Principles of Symbolism Approach and Their Effectiveness in Finding the Meaning of Quranic Symbols - Abdulqayum Tayeb; Habiburrahman Rizapoor (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
Symbolism is one of the significant literary approaches through which various literary, ideological, and scientific texts are analyzed using its concepts. In this study, the symbolic verses of the Holy Quran are interpreted based on the foundational principles of this approach. The primary aim of this work is to determine the extent of symbolism in the Quranic verses and to understand the various viewpoints regarding the "cognitive" and non-"cognitive" nature of the Quranic language. To achieve this goal, a "descriptive-analytical" method has been employed. The findings of this study indicate that the language of the Quran is generally referential and cognitive, meaning there is a meaningful and clear relationship between the signifier and the signified in the concepts of the Quran. In this regard, the "non-cognitive" perspective of the Quranic language, proposed by some thinkers, is not valid, as the language of this divine text is based on common usage and is not limited to any specific group or time. Furthermore, many verses previously considered "symbolic" in earlier studies are not symbols but perceptual metaphors. However, the representation of a limited number of symbols (while retaining their primary meanings) in some Quranic verses cannot be denied. Therefore, these verses can be analyzed and interpreted based on the essential principles of symbolism, such as the originality of imagination, the authenticity of emotions, elevated literary language, and phonetic arrangement.